AB1046 PHYSICAL ACTIVITY ASSESSMENT IN CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS COMPARED TO CONTROLS. (June 2019) - Fazaa, Alia; Sellami, Meriem; Miladi, Saousen; Ouenniche, Kmar; Souabni, Leila; Kassab, Selma; Chekili, Selma; Zakraoui, Leith; Abdelghani, Kawther Ben; Laatar, Ahmed
Abstract : Background: Physical activity (PA), known to maintain optimal metabolic function and normal development could be impaired during Juvenile Idiopathic Arthritis (JIA). Objectives: The aim of our study was to assess PA in children and adolescents with JIA compared to healthy peers using the physical activity questionnaire for children (cPAQ) and adolescents (aPAQ). Methods: This is a cross-sectional study of measured level of PA in children and adolescents with JIA, compared to age and gender-matched healthy Tunisian schoolchildren. PA was estimated by cPAQ and aPAQ filled by the patient group and the reference group. If the child is unable or unsure to answer the questions we have helped with the parents' response. The PAQ scores 2 as "low activity, " >2 and ≤ 3 as "moderate activity, " and >3 as "high to vigorous activity". Results: A total of 55 patients (38 boys and 17 girls) with JIA and 60 healthy control schoolchildren were included. No significant difference in demographic background was found between the two groups. The mean age was 8.5 ± 4.12 years in the JIA group and 9.2 ± 3.51 years in the control group. Thirty-one patients (53%) had persistant oligoarticular JIA, 15 (27%) had polyarticular JIA, 5 patients (9%) had systemic JIA, and 4 (7%) had enthesitis-related arthritis. The median disease duration was 3.2 ± 2.8 years. The mean cPAQ was 2.101 ± 0.722 in the JIA group and 4.112 ± 0.644 in the control group (p=0.0001). Children and adolescents with JIA had a significantly lower levels of PA compared with their healthy peers as assessed by cPAQ/aPAQ (p=0.012). The time spent in each cPAQ/aPAQ item was significantly lower in the JIA group compared to the healthy group: sports activities (3.4 ± 0.5 versus 4.7 ± 1.4 hours/week, p=0.002), leisure time activities (2.2 ± 0.3 versus 6.2 ±1.3 hours/week, p=0.001), activities at school (1.1 ± 0.3 versus 2.1 ± 0.5 hours/week, p=0.001), and after school activities (0.5 ± 0.5 versus 2.5 ± 0.8 hours/week, p=0.001). Seventy six percent of the JIA group spent the day on the two lowest PA categories: sleeping and sitting, which was significantly higher compared with the reference group (p=0.001 and p=0.055, respectively). Conclusion: In our study, children and adolescents with JIA were less physically active than the healthy peers as assessed by the PAQ. More objective methods are needed to better evaluate and quantify the PA. Disclosure of Interests: None declared